Perception of Success among People Practising Martial Arts and Combat Sports - Wojciech J. Cynarski; Przemyslaw Pawelec; Jong-Hoon Yu; Michal Vit; Jan Słopecki; Krzysztof Kubala (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2018)
A scientific framework for this study is the Humanistic Theory of Martial Arts, and the psychology of sport using the concepts of goal, task and success. The problem and aim of this study was an explanation of "perception of success" in groups of adults practising martial arts. Is perception of success influenced by the respondents' social background or the type of martial art practised? Would there be any differences in results depending on their country of origin and residence, and if so, what results? The research was done within the framework of the IMACSSS.1A/2011: "Social determinants of participation in martial arts schools and clubs". The tool was Perception of Success Questionnaire, which was used to survey a number of respondents from the United States, the Czech Republic and Poland, who were selected randomly and participated voluntarily. The statements and calculations have been ranked by more- or - less contact forms of martial arts. The results obtained in this study indicate a poor relationship between perception of success and the type of fighting style practised and a measurable relationship between the perception of success and social origin. There is a weak relationship in perception of success by respondents from American or European cultures.